Case Report: Late Successful Thrombectomy for Ischemic Stroke in a 2-Year-Old Child - Nasr, Nathalie; Delamarre, Louis; Cheuret, Emmanuel; Chausseray, Gerald; Olivot, Jean Marc; Acar, Philippe; Bonneville, Fabrice (Frontiers in Neurology, 2021)
Despite extensive evidence of benefit of thrombectomy in adult ischemic stroke due to large vessel occlusion in the 6-hour window, its role remains uncertain in very young children. We describe hereafter the case of a 2-year-old female child who had a successful thrombectomy 9 hours after stroke onset. The patient presented with right hemiplegia, central facial palsy, a normal level of consciousness and speech difficulties. PedNIHS score was 11. CT scan without contrast injection displayed spontaneous hyperdensity of the middle cerebral artery (MCA), with only limited early signs of ischemia (ASPECTS 8). CT angiography demonstrated occlusion of the proximal MCA with good collaterals.Thrombectomy was realized. Complete recanalization (TICI 3) was obtained under general anesthesia after two passes of a stent-retriever. Time from symptoms onset to full recanalization was 9 hours. The acute ischemic stroke was caused by embolic thrombus from a congenital heart disease. Clinical recovery was complete. Three months after the thrombectomy, the young patient was going well without any neurological sequela (PedNIHSS 0; modified Rankin Scale:0) This case-report is an example of a decision-making process to perform thrombectomy in a very young child, which included cardio-embolic etiology as a parameter that potentially might have participated, in part, to the successful outcome of the therapeutic procedure.